2022
DOI: 10.3390/molecules27031115
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpenes and Monoterpenes from the Leaves and Stems of Illicium simonsii and Their Antibacterial Activity

Abstract: Two undescribed ether derivatives of sesquiterpenes, 1-ethoxycaryolane-1, 9β-diol (1) and 2-ethoxyclovane-2β, 9α-diol (3), and one new monoterpene glycoside, p-menthane-1α,2α,8-triol-4-O-β-D-glucoside (5), were obtained, together with eight known compounds from the stems and leaves of I. simonsii. Their structures were elucidated by spectroscopic methods. Compounds 1–11 were evaluated for their potency against Staphylococcus aureus and clinical methicillin-resistant S. aureus (MRSA). Among them, compound 3 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The antibacterial activity of monoterpene-rich essential oil has been attributed to the inhibition and eradication of biofilm formation [58,64] and increases in membrane permeability, which allow higher amounts of test samples to enter pathogenic cells and consequentially destroy them [65]. In addition, Li et al [66] demonstrated the antibacterial activity (MIC values: micromolar range) of a number of monoterpenes isolated from Illicium simonsii stems and leaves. Li's group attributed the observed antibacterial activity of Illicium simonsii monoterpenes to the disruption of the bacterial membrane permeability, as revealed by 4 ′ ,6-diamidino-2-phenylindole (DAPI) and propidium iodide (PI) assays [66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibacterial activity of monoterpene-rich essential oil has been attributed to the inhibition and eradication of biofilm formation [58,64] and increases in membrane permeability, which allow higher amounts of test samples to enter pathogenic cells and consequentially destroy them [65]. In addition, Li et al [66] demonstrated the antibacterial activity (MIC values: micromolar range) of a number of monoterpenes isolated from Illicium simonsii stems and leaves. Li's group attributed the observed antibacterial activity of Illicium simonsii monoterpenes to the disruption of the bacterial membrane permeability, as revealed by 4 ′ ,6-diamidino-2-phenylindole (DAPI) and propidium iodide (PI) assays [66].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Li et al [66] demonstrated the antibacterial activity (MIC values: micromolar range) of a number of monoterpenes isolated from Illicium simonsii stems and leaves. Li's group attributed the observed antibacterial activity of Illicium simonsii monoterpenes to the disruption of the bacterial membrane permeability, as revealed by 4 ′ ,6-diamidino-2-phenylindole (DAPI) and propidium iodide (PI) assays [66]. A number of previous reports [67][68][69] have also pointed out efflux pump as one of the mechanisms by which monoterpene-rich essential oils exert antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many studies have shown that monoterpenoids and sesquiterpenoids are considered excellent alternatives for antifungal and antibacterial agents due to their wide-reaching bioactivities and abundance of structural skeletal types. [80][81][82] To the best of our knowledge, no prior research has looked into how the essential oil of this sap affects the mycelial growth of FOL. This work is the rst to address this activity, and it is interesting to see that HC-AKA-EO has a strong antifungal effect against FOL.…”
Section: Antifungal Activitymentioning
confidence: 99%
“…ISM, a member of Illicium L., is mainly indigenous in India, Myanmar, and the southwestern part of China [ 10 ]. In addition, the research on ISM mainly focuses on the separation of its chemical compounds and pharmacological activities, such as anti-inflammatory [ 11 ], antibacterial [ 12 ], and neuroprotective effects [ 13 ]. In addition, anisatin and (1S)-minwanenone separated from ISM can inhibit the growth of SMMC-7721 cells [ 14 ].…”
Section: Introductionmentioning
confidence: 99%